Successful Treatment of Keloid with Weekly Intralesional Triamcinolone Acetonide (40%) And 5-Fluorouracil Combination: A Case Report - Sutedja, Eva Krishna; Sutedja, Endang; Ruchiatan, Kartika; Faldian, Yogi; Yogya, Yuri; Avriyanti, Erda; Firdaus, Chaerani Pratiwi; Firdaus, Mohammad Rizky (Journal of Neonatal Surgery, 2025)
Keloids often cause significant physical discomfort and psychological distress, profoundly impacting patients' quality of life. Intralesional therapy combining triamcinolone acetonide (TA) and 5-fluorouracil (5-FU) has emerged as a promising treatment option, with demonstrated efficacy in clinical studies. Although most protocols advocate injection intervals of 2–3 weeks, weekly administration has been explored in some studies. However, data on the efficacy and safety of this combination therapy particularly in Asian populations remain limited. This case report describes the successful use of intralesional 5-FU combined with 40% TA for keloid treatment, demonstrating efficacy with minimal adverse effects. A 42-year-old woman with a history of surgical excision presented with a solitary, irregularly shaped, well-defined, hyperpigmented, and pruritic tumor in the pubic region. Following an initial cryotherapy session, the patient underwent weekly intralesional injections of 40% TA and 5-FU in a 1:9 ratio for six weeks. The patient experienced mild to moderate procedural pain, with a Visual Analog Scale (VAS) score of 3–5, and developed ulceration at the injection site after the sixth session. Despite the absence of a standardized protocol for this combination therapy, significant clinical improvement was observed, with the keloid size reducing from 6 × 3.5 × 0.8 cm to 4.9 × 2.4 × 0.1 cm . This case highlights the weekly intralesional combination of 40% TA and 5-FU as an effective treatment for keloid reduction, offering tolerable side effects and favorable patient outcomes